Market Entry Strategy of Multinational Enterprise (MNE): A Case Study of Harley Davidson - Ria Triwastuti (Universitas Airlangga, 2017)
Harley Davidson America has been facing internationalisation issue from economic and social forces. Besides some potentials of entering emerging market, there are some challenges to be encountered by Harley Davidson such as political-economy and cultural differences between USA and India. This study elaborates and evaluates the strategy of Harley Davidson USA to expand its market to India. The method used in this paper is a qualitative analysis with case study approach, supported by a few quantitative data. Data collected from the publicly available documents related Harley Davidson. The study finds that entry market strategy conducted by Harley Davidson is effective and favourable for the firm though it has several potential risks.